OPTIMISASI PENDISTRIBUSIAN TELUR MENGGUNAKAN MODEL FUZZY MULTIOBJECTIVE CYCLICAL INVENTORY ROUTING PROBLEM - Mukminah Mardiah; Fibri Rakhmawati; Rina Filia Sari (LPPM Universitas Bina Bangsa, 2023)
The distribution of duck eggs is carried out in several retail stores in Medan, where road conditions, vehicle conditions and travel times are uncertain which results in uncertain costs. This problem can be solved using a fuzzy model that aims to minimize costs and minimize delivery time. This research was conducted at CV. Bebek Berkah Farm by discussing the Optimization of Egg Distribution using the FMOCIRP model. Completion of this model is done by using Winqsb software. Based on the results of calculations, the FMOCIRP model can save with an initial cost of 114,000 to Rp.84.500, and delivery time to 239 minutes from 277 minutes previously, where the optimal solution is a distribution route that provides minimum costs and time